Distúrbios psíquicos menores em enfermeiros docentes - Tavares, Juliana Petri (2010)
This study investigates the psychological demand and job control (quadrants of the demandcontrol model) associated with minor psychiatric disorders (MPD) in nursing faculty. Sectional study including 130 nursing faculty members at the federal universities of Rio Grande do Sul, Brazil. For assessment of psychological distress and dimensions of the demand-control model, we used the Brazilian versions of the Self-Report-Questionnaire (SRQ-20) and the Job Stress Scale (JSS), respectively. Was used to enter data Epi Info ®, version 6.4, with independent double entry and analysis program SPSS ® Statistic (Predictive Analytics Software from SPSS Inc., Chicago - USA) version 18.0 for Windows. After the descriptive analysis, there were the bivariate and multivariable, adopting a level of 95% (p <0.05). The nursing professors were predominantly female (90.8%) with average age of 47 (± 4.65) years old, had a doctorate (56.9%), belonged to the white race (93.1%), were married or lived with a partner (74.6%), had one or two children (50%), had per capita family income of up to six times the minimum wage (50.5%) and had up to three dependents (73.8%). Regarding employment data, 50% of nursing professors belonged to the category professional assistant, followed by assistant category (36.9%). The system of work, 93.1% worked 40 hours per week full-time, 30% worked more than 20 years, developing teaching at undergraduate (50.8%) for undergraduate and postgraduate studies (49, 2%), research activities (91.5%) and extension (85.4%). The prevalence of minor psychiatric disorders was 20%. After adjustments for potential confounders, the odds of suspected mental disorder was higher in the quadrant active work (OR = 14.23, 95% CI 1.55 to 130.73), followed by highstrain quadrant (OR = 10.05; 95% CI = 1.23 to 82.44) compared to nursing professors in lowstrain quadrant. We conclude that high psychological demands and low job control may trigger bouts, including the MPD in nursing faculty. It is evident also that the high psychological demand has a negative influence on the work of nursing faculty members, even when these workers have high job control. Therefore, some individual strategies and organizational issues need to be rethought in order to prevent the mental illness of nursing professors.